2022
DOI: 10.1021/jacs.2c09241
|View full text |Cite
|
Sign up to set email alerts
|

High-Spin S = 3/2 Ground-State Aminyl Triradicals: Toward High-Spin Oligo-Aza Nanographenes

Abstract: We report high-spin aminyl triradicals with near-planar triphenylene backbones. Near-planarity of the fused aminyl radicals and the 2,6,10-triphenylene ferromagnetic coupling unit (FCU), magnetically equivalent to three fused 3,4′-biphenyl FCUs, assures an effective 2pπ–2pπ overlap within the cross-conjugated π-system, leading to an S = 3/2 (quartet) ground state that is well separated from low-spin excited doublet states. Thermal populations of the low-spin (S = 1/2) excited states are detectable both by SQUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 96 publications
4
55
0
Order By: Relevance
“…Indeed, in any of the resonance forms depicted in Figure , each pair of radicals is separated by an odd number of π-conjugated carbon atoms, which should result in a parallel arrangement of the spin centers. Similar behavior has been reported recently for aminyl triradicals with a cross-conjugated π-system . In contrast, the loss of conjugation leads to weakening of the intramolecular spin correlations, as was shown for several systems with variable strength and sign of intramolecular magnetic exchange.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, in any of the resonance forms depicted in Figure , each pair of radicals is separated by an odd number of π-conjugated carbon atoms, which should result in a parallel arrangement of the spin centers. Similar behavior has been reported recently for aminyl triradicals with a cross-conjugated π-system . In contrast, the loss of conjugation leads to weakening of the intramolecular spin correlations, as was shown for several systems with variable strength and sign of intramolecular magnetic exchange.…”
Section: Resultssupporting
confidence: 87%
“…Similar behavior has been reported recently for aminyl triradicals with a cross-conjugated π-system. 25 In contrast, the loss of conjugation leads to weakening of the intramolecular spin correlations, as was shown for several systems with variable strength and sign of intramolecular magnetic exchange. For example, a pronounced temperature dependence of χT was observed in a series of nitroxide triradicals, due to weaker ferromagnetic exchange that led to the room-temperature χT value being much closer to 1.125 emu K mol −1 , expected for three noninteracting S = 1/2 centers.…”
Section: ■ Results and Discussionmentioning
confidence: 81%
“…So, the search for stable non-Kekulé diradicaloids continues (Figure ). Very recently, Juríček and co-workers reported that trimesityltriangulene is persistent, while the groups of Wu and Rajca reported high-spin nitrogen-doped nanographenes.…”
Section: Resultsmentioning
confidence: 99%
“…2,2′-Biphenylene-fused tetrazolinyl (BFTZ) monoradicals, or so-called phototetrazolinyl radicals, have attracted our attention because of their exceptional stability and, most importantly, the potential to achieve relatively large spin densities at the para -positions (and ortho -positions) with respect to the nitrogens of the tetrazolinyl moiety (Figure ). Large spin densities at the para / ortho positions are the essential prerequisite in the design of high-spin polyradicals with large energy gaps between the high-spin ground state and low-spin excited state. …”
Section: Introductionmentioning
confidence: 99%